Pengaruh Hedonic Shopping, Lifestyle Dan Shopping Enjoyment Terhadap Impulse Buying Yang Dimediasi Product Browsing Di Tiktok Shop Pada Mahasiswa Univeristas Muhammadiyah Sumatera Utara - Diana Sari Harahap; Nadia Ika Purnama; Seprida hanum (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
The purpose of this study is to determine and analyze the direct effects of hedonic shopping, lifestyle, shopping enjoyment, and product browsing on impulse buying; to examine and analyze the direct effects of hedonic shopping, lifestyle, and shopping enjoyment on product browsing; and to investigate and analyze the indirect effects of hedonic shopping, lifestyle, and shopping enjoyment on impulse buying through product browsing. This study employed an associative research design with a sample of 100 respondents, consisting of students from Universitas Muhammadiyah Sumatera Utara who are users of TikTok Shop. Data were collected using a structured questionnaire, and the data were analyzed using the Partial Least Squares (SmartPLS) method. The results indicate that hedonic shopping, lifestyle, shopping enjoyment, and product browsing have direct effects on impulse buying. Furthermore, hedonic shopping, lifestyle, and shopping enjoyment have a positive and significant direct effect on product browsing, and they also have a positive and significant indirect effect on impulse buying through product browsing.